The Effects of Physical Resources on the Implementation of Inclusive Education in Public Secondary Schools – Kenya (International Journal of Scientific Research and Management (IJSRM), 2019)
Educational frameworks and Kenyan constitutions mandate schools to adopt; design and implement programmes that support inclusive education. Despite the inclusive education policy, disability remains a major course of exclusion in public secondary schools in Kenya. The study evaluated the influence physical resources towards the implementation of inclusive education in Kenyan schools. The study employed mixed method research design which uses both qualitative and quantitative methods. Purposive sampling technique was used to select 201 respondents from 18 extra-county and county public secondary schools that had enrolled learners with physical disabilities. Quantitative data was collected using questionnaires while qualitative data was collected through interviews and focus group discussions. A t-test was used to test the significance and determine whether to reject or accept the study hypotheses. An analysis of the findings indicated significant relationships between physical resources and implementation of inclusive education. The Linear Model showed a moderate positive correlation between human resource and inclusion. The model further showed that the rate of physical resource accounted for some variation towards the implementation of inclusive education. Creating an inclusive school where physical resources are modified and restructured to respond to learner diversity is a complex process with many inter-related elements. The schools should have a collaborative approach by creating back-up partnerships with parents, the community and disability associations. There is a need mobilize all key stakeholders to modify physical resources in order to overcome barriers that hamper access and participation in the learning process